A multimethod-investigation of the adsorption of ethylene oxide on Ni(110) - Weinelt, M.; Zebisch, P.; Steinrück, Hans-Peter (Surface Science, 1993)
The adsorption of ethylene oxide on Ni(110) has been studied by TPD, work function measurements, LEED, XPS, and angle resolved UPS using linearly polarized synchrotron radiation. At temperatures below 100 K ethylene oxide adsorbs in molecular form on Ni(110) with a saturation coverage of ∼ 0.5 ML (1 ML = 1 molecule Ni atom). Upon heating, molecular desorption occurs in a broad peak ranging from ∼ 110 to 240 K; there is no indication of dissociation, as concluded from TPD and XPS. At saturation a sharp c(2 × 2) LEED pattern is observed. From ARUPS we deduce that the C rotation axis of the molecule is tilted away from the surface normal and that the mirror planes of the molecule do not coincide with the substrate mirror planes, independent of coverage. © 1993.